Project Based on Environment Learning dan Literasi Lingkungan dalam Kaitannya dengan Creative Thinking Skill - Alya Qhutra Nada Salym; Sumarmi Sumarmi; Hadi Soekamto; Sharina Osman (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This research is a study using a project-based learning model on environment learning and its influence on creative thinking skills in terms of students' environmental literacy skills. This research was conducted to integrate the creative thinking ability of students with the level of environmental literacy of students who have a positive impact directly on the environment and society. This research has a posttest-only control group design and is a quasi-experiment. Students from SMAN 4 Sidoarjo's class 11 geography course participated as the study's subjects. The determination of experimental and control classes are carried out randomly. The result is that class 11 of Geo 3 specialization is selected as the experimental class while class 11 of Geo 2 specialization as the control class. Data collection using creative thinking ability test instruments and environmental literacy questionnaires. The Independent Sample T-Test and the Two Way Anova test were applied for the statistical analysis using the SPSS 26.0 version for Windows. The research revealed that (1) students' capacity for creative thought is positively impacted by the Project Based on Environment Learning model with a sig value. 0.003 0.05; (2) the project- based environmental learning model has a beneficial impact on students' capacity for original thought in terms of environmental literacy with sig values. 0.037 0.05.